BETWEEN FRAMES AND DREAMS: PSYCHOANALYTIC REFLECTIONS ON WAKING LIFE AND CINEMA IN NANPAKAL NERATHU MAYAKKAM - C R, Ancy; Pai, Geetha R (International Journal of Research -GRANTHAALAYAH, 2025)
Dreams have been analysed in various fields like psychoanalysis and psychology. This article will explore how the conscious mind is affected by the dream and how it becomes the material for satisfying or fulfilling one’s unconscious desire or innermost aspirations, which are often unnoticed and it investigates how it derives its material from reality and the day-to-day psychic encounters of the dreamer, consciously or unconsciously. Furthermore, the article will conduct an investigation into the relationship between dreams and waking life in psychoanalysis using Nanpakal Nerathu Mayakkam’s cinematic approach. The main purpose of this article is to analyse the question: do physical states influence mental states? Do mental states influence physical states? If so, how? Additionally this article employs psychoanalytic film theory to inquire into how an openly ended film with its various narrative methods and visual techniques, creates a complex visual experience for the audience. This research makes an important contribution to the deeper discourse on psychoanalysis and cinema, by providing a framework that connects theoretical ideas with visual narratives. It emphasises film’s efficacy as a medium for investigating into the intricate layers of the human mind as well as psychology.